Kajian Transportasi Sungai Untuk Menghidupkan Kawasan Tepian Sungai Kahayan Kota Palangkaraya - Noor Hamidah; R Rijanta; Bakti Setiawan; Muh Aris Marfai (Diponegoro University, 2014)
River is a first transportation for connection city to village and central for economic community. Nowadays, land transportation is a trend for connection city to village. River transportation have been not priority, due to land transportation more easy to access, low cost and faster rather than river transportation. River have been not priority for infrastructure and river is a backward. River is facing serious problems such as physical and environmental problem. River are still occupy for lower income people as a reason house can built by themselves and close to work location with a location in green belt area. Thispaper try to arguehow is a problem in river transportation. The location of this research is Kahayan River, Palangkaraya City. This research aim is to reveal of potential of river transportation and unique of moda transportation will be revitalize of Kahayan riverside area of Palangkaraya City, Central Kalimantan.River is a first transportation for connection city to village and central for economic community. Nowadays, land transportation is a trend for connection city to village. River transportation have been not priority, due to land transportation more easy to access, low cost and faster rather than river transportation. River have been not priority for infrastructure and river is a backward. River is facing serious problems such as physical and environmental problem. River are still occupy for lower income people as a reason house can built by themselves and close to work location with a location in green belt area. Thispaper try to arguehow is a problem in river transportation. The location of this research is Kahayan River, Palangkaraya City. This research aim is to reveal of potential of river transportation and unique of moda transportation will be revitalize of Kahayan riverside area of Palangkaraya City, Central Kalimantan.